The Effects of Proprioceptive Exercises on Postural Control in Handball Players with Chronic Ankle Instability-A Non-Randomized Control Trial - Bogdan-Alexandru Antohe; Elena-Adelina Panaet (MDPI AG, 2024)
Background: This paper aims to investigate the impact of proprioceptive exercises on postural control in handball players with chronic ankle instability. Methods: The research participants (n = 22) were divided into two groups: the experimental group (n = 11) and the control group (n = 11). Chronic ankle instability was diagnosed using the Identification of Functional Ankle Instability (IdFAI) questionnaire, while postural control was evaluated with the Iso-Shift stabilometric platform. The intervention consisted of a 15-week proprioceptive exercise program, with sessions performed three times a week. The rehabilitation protocol was conducted at the start of each training session, immediately following the warm-up. Results: The data were analyzed using the Wilcoxon and Mann-Whitney U tests. Both groups improved their score on the Identification of Functional Ankle Instability (IdFAI) questionnaire (IdFAI_CG, p < 0.011; IdFAI_EG, p < 0.003) and reduced the number of ankle sprains (NS_EG, p < 0.008). Also, the experimental group had better results for the following tests: ellipse area with open eyes on the left leg (EA_I-OE_L, p < 0.009), ellipse area with closed eyes on the left leg (EA_I-CE_L, p < 0.033), anteroposterior deviation with open eyes on the left leg (APD_I-OE_L, p < 0.023), and the initial and final number of ankle sprains (NS_I, p < 0.01; NS_F, p < 0.024). Conclusions: Athletes who suffer from chronic joint instability are more likely to experience severe postural deviations than those who do not have this condition. Proprioceptive exercises had a positive impact on postural control in both groups, but the experimental group showed a greater improvement.